Review of a priori dietary quality indices in relation to their construction criteria - Christine Burggraf; Ramona Teuber; Stephan Brosig; Toni Meier (Nutrition Reviews, 2018)
A multitude of indices measure the healthiness of dietary patterns. Because validation results with respect to health outcomes do not sufficiently facilitate the choice of a specific dietary quality index, the decision of which index to use for a particular research objective should be based on other criteria. This review aims to provide guidance on which criteria to focus upon when choosing a dietary index for a specific research question. A review of 57 existing specifications of dietary quality indices was conducted, taking explicitly into account relevant construction criteria explicated in the Organisation for Economic Co-operation and Development handbook on constructing composite indicators. Index construction choices regarding the following criteria were extracted: theoretical framework, indicator selection, normalization and valuation functions, and aggregation methods. Preferable features of dietary indices are discussed, and a summarizing toolbox is provided to help identify indices with the most appropriate construction features for the respective study aim and target region and with regard to the available database. Directions for future efforts in the specification of new diet quality indices are given.
Keywords: 330; diet quality; dietary quality index; index specification